A Randomized Comparison of Anthropomorphic Changes With Preferred and Alternative Efavirenz-Based Antiretroviral Regimens in Diverse Multinational Settings - Erlandson, Kristine M. (Open Forum Infect Dis, 2015)
Background. Existing data on anthropomorphic changes in resource-limited settings primarily come from observational or cross-sectional studies. Data from randomized clinical trials are needed to inform treatment decisions in these areas of the world. Methods. The AIDS Clinical Trials Group Prospective Evaluation of Antiretrovirals in Resource-Limited Settings (PEARLS) study was a prospective, randomized evaluation of the efficacy of emtricitabine/tenofovir + efavirenz (FTC/TDF + EFV) vs lamivudine/zidovudine + efavirenz (3TC/ZDV + EFV) for the initial treatment of human immunodeficiency virus (HIV)-1-infected individuals from resource-diverse settings. Changes in anthropomorphic measures were analyzed using mixed-effect models for repeated measurements, using all available measurements at weeks 48, 96, and 144. Intent-to-treat results are presented; as-treated results were similar. Results. Five hundred twenty-six participants were randomized to FTC/TDF + EFV, and 519 participants were randomized to 3TC/ZDV + EFV. Significantly greater increases from baseline to week 144 were seen among those randomized to FTC/TDF + EFV vs 3TC/ZDV + EFV in all measures except waist-to-hip ratio, with the following mean changes: weight, 4.8 vs 3.0 kg; body mass index, 1.8 vs 1.1 kg/m(2); mid-arm, 1.7 vs 0.7 cm; waist, 5.2 vs 4.3 cm; hip, 3.8 vs 1.4 cm; and mid-thigh circumference, 3.1 vs 0.9 cm. There were 7 clinical diagnoses of lipoatrophy in the 3TC/ZDV + EFV arm compared with none in the FTC/TDF + EFV arm. The proportion of overweight or obese participants increased from 25% (week 0) to 42% (week 144) for FTC/TDF + EFV and from 26% to 38% for 3TC/ZDV + EFV. Conclusions. Our findings support first-line use of FTC/TDF + EFV in resource-limited settings and emphasize the need for interventions to limit weight gain among overweight or obese HIV-infected participants in all settings.